Pragmatisme Politik dalam Pemilu Legislatif Tahun 2024 di Kabupaten Lamongan - Sejati, Satryo Pringgo; Hakim, Ahmad Burhan (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Political pragmatism and democracy in Indonesia are so massive, and this also happens in the regions, including Lamongan Regency. High political costs are one of the significant factors in the occurrence of pragmatic politics. So it is difficult to avoid or even eliminate. The research method in this simple article is a qualitative research method using library studies and interviews to obtain the required data, both primary and secondary data. Lamongan Regency is a regency known as the City of Santri or the City of Wali, from there the Regency rose to be researched. Liberal democracy that is developing in Indonesia creates new social facts in society. These facts are the existence of pragmatic political practices and transactional politics that cause extraordinary high-cost politics, so today's Indonesian democracy cannot be separated from these facts. Moreover, society also has quite pragmatic and transactional thinking when the election arrives. So that this does not happen in a vacuum, but in fact it happens so massively that it seems to be an open secret for society and political leaders themselves.